Perlindungan Hukum Terhadap Jual Beli Tanah yang Dilakukan dengan Itikad Baik - Handy Firman; Gunawan Gunawan (UNES Law Review, 2023)
Land transactions play a crucial role in social and financial aspects, particularly concerning property ownership. The integrity and good faith of involved parties in these transactions are pivotal in legal protection, especially in safeguarding well-intentioned buyers. This study aims to explore the legal framework, challenges, and outcomes regarding land transactions involving buyers with good intentions, focusing on Indonesian law. The objective is to examine the existing legal framework, challenges, and outcomes associated with such transactions to ensure fair and proper practices. This research adopts a normative approach, emphasizing an in-depth analysis of existing legal texts, court decisions related to cases involving buyers acting in good faith during land transactions, and relevant legal documents. The primary focus is on "written law," exploring statutes, government regulations, and court decisions related to these transactions. Key findings highlight the significance of good faith in contractual agreements, regulated in the Indonesian Civil Code. Buyers acting in good faith during land transactions are entitled to legal protection according to Article 1338 of the Civil Code. This principle, reinforced by Circular Letter No. 7/2012, safeguards honest buyers even when the seller lacks valid property rights. However, complexities in law enforcement arise due to conditions for valid agreements, land registration, and the pivotal role of a notary or Land Deed Official (PPAT) in the transaction process.